Karakteristik dendeng daging lumat ikan tongkol dengan penambahan tepung rumput laut Gracilaria sp.: Characterization of tuna jerky with the addition of seaweed (Gracilaria sp.) flour - Lobo, Reni; Roiska, Riris; Wulandari, Tri; Soselisa, Julian Franklin; Zulfamy, Kristian Edo (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Fish jerky has a hard texture, which makes it less attractive to consumers. The aim of this study was to determine the concentration of Gracilaria sp., the best seaweed flour, to determine the characteristics of crushed tuna jerky (Euthynnus affinis). The research method used in this study was a Completely Randomized Design with one treatment and three replicates. Data were analyzed using analysis of variance (ANOVA) and preference levels using Kruskal-Wallis analysis. Result shown that seaweed flour characterization was consisted dietary fiber 75,32±0,69%, viscosity 5.52±0.01 cPs, gel strength 40.65±0.04 g/cm2, agar 32.22±0.01%, heavy metal Hg was <0.002 ppm, Pb was <0.004 ppm and Cd was 0.063±0.001 ppm, water content 11.77±0.34% and yield 14.02±0.06%. Based on the research results, the addition of 2.5% Gracilaria sp. flour resulted in high-quality jerky with an appearance value of 7.67, flavor of 7.30, texture of 7.60, and taste of 7.03 from 1-9 scales. The result of the paired comparison test against commercial jerky (beef) was positive, which means that the quality of tuna jerky was better than that of commercial jerky and was well accepted by the panelists. Proximate analysis of tuna jerky shown that protein content 34.36±0.01%, water 10.56±0.15%, lipid 3.08±0.44% and ash 6.30±0.05%. Texture analysis results shown hardness of 976.67±189.11, adhesiveness of 0.24±0.18 and fracture of 12.96±3.56.